PENGARUH GOOD CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP KINERJA KEUANGAN PADA PT BANK SINARMAS TBK PERIODE 2013-2023 - Rahma, Rahmawati; Zaman, Muhamad Badru (Journal of Research and Publication Innovation, 2024)
This study aims to determine whether Good Corporate Governance projected with Institutional Ownership and Profitability projected with Net Profit Margin affect the Financial Performance projected with Return On Assets at PT Bank Sinarmas Tbk, Period 2013-2023. This study uses associative research methods with a quantitative approach. The population used in this study is the entire Financial Statements of PT Bank Sinarmas Tbk, while the sample used is the financial position report, income statement and notes to the financial statements at PT Bank Sinarmas Tbk, 2013-2023 Period. The analysis method used is descriptive statistical test, classical assumption test, regression analysis test, correlation coefficient test, determination coefficient test, and hypothesis testing using the SPSS 26 program. Based on hypothesis testing with the T test, it shows that partially the Institutional Ownership variable has no significant effect on Return On Assets with a tcount value < ttable (0.542 < 2.30600) and a significance value > the significance level (0.602 > 0.05). Meanwhile, the Net Profit Margin variable partially has a significant effect on Return On Assets with a tcount> ttable value (10.759> 2.30600) and a significance value < significant level (0.000 < 0.05). The results of hypothesis testing with the F test show that simultaneously the Institutional Ownership and Net Profit Margin variables have a significant effect on Return on Assets with a value of Fhitung> Ftabel (99.202> 4.26) and a significance value < significant level (0.000 < 0.05). The coefficient of determination of 0.961 or 96.1% proves that the Institutional Ownership and Net Profit Margin variables have an influence of 96.1% on Return on Assets (Y), while the rest (100% - 96.1% = 3.9%) there are other factors that have not been studied.